Décolonisant l'argent à Porto Rico - Negrón-Muntaner, Frances (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Writing Art Histories From Below: A Decolonial Guanaca-Hood Perspective - Cornejo, Kency (Latin American and Latinx Visual Culture, 2019)
As a teenager during my first internship at the Los Angeles County Museum of Art, a diversity initiative for inner-city youth, the education curator enthusiastically asked, “Who here would like to be an art historian!?” Like all the other Black and Brown inner-city kids, I laughed inside. My response was not due to a lack of art appreciation; I grew up in a family of refugees who were all self-taught artists back home in El Salvador, who taught me to draw before I learned to read. Nor was my response rooted in apathy for creative expression, for I was involved in art and theater from my elementary through my high school years. Art was such a natural part of my life that the idea of studying it seemed wasteful to me. The truth was, the internship was one of two jobs I was working to financially help my family and pay for my first year of community college. Hidden even deeper, though, I believed the museum world was not my world. I was a guanaca (the appellative given to people from El Salvador) whose family fled war and remained invisible in mainstream US Latinx history and culture. I was also from the hood—in my case Compton, California, a city made notorious by gangsta rap and police brutality. I believed that people like me guarded the art on the museum walls, cleaned the floors and bathrooms for visitors, and served the food at the high-priced café. People who looked like me, who came from where I did, did not determine what art could be, nor could we afford to buy it. We certainly did not write the history of art, for if we had, we would see ourselves represented on the walls.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé